2009
DOI: 10.1055/s-0029-1218595
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonic Acid Functionalized Silica: A Mild, Reusable and Efficient Heterogeneous Catalyst for the Highly Diastereoselective Synthesis of cis-Isoquinolonic Acids

Abstract: Sulfonic acid functionalized silica (SAFS) is found to be a recyclable heterogeneous catalyst for the rapid and efficient synthesis of various cis-isoquinolonic acids from the three-component condensation reaction of homophthalic anhydride, an amine, and an aldehyde. This reaction was highly diastereoselective and only one diastereomer was obtained in all cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Recently, Karimi et al 366 have reported the use of sulfonic acid functionalized silica (SAFS) as a recyclable heterogeneous catalyst for the synthesis of isoquinolonic acids by a three component condensation of homophthalic anhydride, aldehydes and amines. When the reaction was carried out at room temperature in the presence of acetonitrile, good yields of the isoquinolonic acid derivatives were obtained (78-98%) in 1-5 h. The reaction was highly diastereoselective and only the cis diasteromer was obtained in all cases.…”
Section: Tetrahydroisoquinolonic Acid Derivativesmentioning
confidence: 99%
“…Recently, Karimi et al 366 have reported the use of sulfonic acid functionalized silica (SAFS) as a recyclable heterogeneous catalyst for the synthesis of isoquinolonic acids by a three component condensation of homophthalic anhydride, aldehydes and amines. When the reaction was carried out at room temperature in the presence of acetonitrile, good yields of the isoquinolonic acid derivatives were obtained (78-98%) in 1-5 h. The reaction was highly diastereoselective and only the cis diasteromer was obtained in all cases.…”
Section: Tetrahydroisoquinolonic Acid Derivativesmentioning
confidence: 99%
“…The CCR also forms the basis of a three-component reaction (3CR) of homophthalic anhydride, amines, and aldehydes with Lewis acid catalysts and additives. In one case, a diacid is used as an anhydride precursor . Similar zwitterionic intermediates were proposed for the 3CR of homophthalic anhydride with amines and aldehydes, wherein the amine attacks homophthalic anhydride to form amide-acid 11 , followed by condensation with aldehyde 9 and successive Mannich addition (Figure A) .…”
Section: Introductionmentioning
confidence: 88%
“…Recently, 3,4trans-isoquinolonic acids have been prepared without catalyst by heating homophthalic anhydride IVa with different amines and aldehydes in the presence of Na 2 SO 4 in refluxing toluene [20]. 3,4-cis-isoquinolonic acids have been prepared in the presence of ionic liquids [21], trimethyl orthoformate [22], Yb(OTf) 3 [23], silica sulfuric acid [24], sulfonic acid functionalized silica [25], KAl(SO 4 ) 2 •12H 2 O [26], or L-proline [27]. The formations of cis-isoquinolonic acids under the conditions described above took several hours at room temperature or reflux in different solvents (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%